2015
DOI: 10.1016/j.chom.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA let-7 Modulates the Immune Response to Mycobacterium tuberculosis Infection via Control of A20, an Inhibitor of the NF-κB Pathway

Abstract: The outcome of the interaction between Mycobacterium tuberculosis (Mtb) and a macrophage depends on the interplay between host defense and bacterial immune subversion mechanisms. MicroRNAs critically regulate several host defense mechanisms, but their role in the Mtb-macrophage interplay remains unclear. MicroRNA profiling of Mtb-infected macrophages revealed the downregulation of miR-let-7f in a manner dependent on the Mtb secreted effector ESAT-6. We establish that let-7f targets A20, a feedback inhibitor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
196
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(204 citation statements)
references
References 50 publications
7
196
1
Order By: Relevance
“…Furthermore, emerging evidence indicates that certain single let-7 family members play individual roles in different types of immune cells. For example, let-7f modulates macrophage immune response to infection by Mycobacterium tuberculosis through repressing A20 (Kumar et al, 2015), whereas let-7a plays a pro-inflammatory role in an experimental asthma model by targeting IL-13 (Kumar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging evidence indicates that certain single let-7 family members play individual roles in different types of immune cells. For example, let-7f modulates macrophage immune response to infection by Mycobacterium tuberculosis through repressing A20 (Kumar et al, 2015), whereas let-7a plays a pro-inflammatory role in an experimental asthma model by targeting IL-13 (Kumar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A20 inhibits inflammation through interfering with NF-B, MAPK, and interferon regulatory factor pathways and regulates cellular functions, including apoptosis, necroptosis, and autophagy, in several models of inflammatory diseases and cell types (28). Furthermore, increased A20 expression or activity has also been associated with dampening numerous disease outcomes (29,30). Thus, there is great interest in manipulating A20 for therapeutic benefit (31).…”
Section: Tlr9 and A20 In Periodontal Inflammationmentioning
confidence: 99%
“…It is possible that, although it is still a functional protein in the course of periodontitis, A20 expression does not reach sufficient levels to facilitate the resolution of inflammation. Thus, the questions that remain to be answered are how A20 levels and activity are regulated and whether the manipulation of A20 can prevent further periodontal tissue destruction, similar to its effects in other inflammatory diseases (29)(30)(31).…”
Section: Tlr9 and A20 In Periodontal Inflammationmentioning
confidence: 99%
“…It remains speculative whether let-7 modulates IL-10 production in this setting, and if the generation of an immunosuppressive milieu confers a survival benefit for HIV-1 [71]. Another study has shown that in macrophages infected with Mycobacterium tuberculosis, let-7 is downregulated, which in turn promotes bacterial survival and suppresses responses [72]. In a recent study, Ansel and colleagues described the effect of the miR-17ß92 cluster, particularly miR-19a, in the control of Th2-type responses.…”
Section: Mirna Regulation Of Il-2mentioning
confidence: 99%